Intraoperative fluid management in hepato-biliary-pancreatic operation using stroke volume variation monitoring: A single-center, open-label, randomized pilot study. Issue 50 (11th December 2020) - Iwasaki, Yudai; Ono, Yuko; Inokuchi, Ryota; Ishida, Tokiya; Kumada, Yoshibumi; Shinohara, Kazuaki
Abstract: Trial design: This investigator-initiated, single-center, open-label, parallel-group, randomized-controlled pilot study was designed to compare the intraoperative fluid balance and perioperative complications in patients undergoing hepato-biliary-pancreatic surgery with or without stroke volume variation (SVV)-guided fluid management. Methods: Patients who were aged >18 years and underwent elective major hepato-biliary-pancreatic surgery between June 30, 2015, and August 31, 2016 at our center were randomly assigned to receive SVV-guided or conventional fluid therapy. The intervention group used SVV to determine the patients' volume status. The primary outcome was the total fluid balance per body weight per operation time, and the secondary outcomes were the total amount of intravenous infusion per body weight per operation time and the Sequential Organ Failure Assessment score on postoperative day 1. Patients were randomized by a two-block computer-generated assignment sequence. Masking of patients and assessors was conducted. The patients and assessors were each blinded to the details of the trial; however, the clinicians were not. Results: Of the 69 patients who were initially eligible, 60 provided informed consent for participation in the study. After randomization, three patients dropped out of the study because of deviations from the protocol or unexpected hypotension, leaving 28 and 29 patients in the intervention and control groups, respectively. Patients in both groups had similar characteristics at baseline. The median (interquartile range [IQR]) intraoperative fluid balance in the control and SVV groups was 6.2 (IQR, 4.9–7.9) and 8.1 (IQR, 5.7–10.5) ml/kg/h, respectively ( P  = .103). The administered intravenous infusion was significantly higher in the SVV group (median, 10.9; IQR, 8.3–15.3 ml/kg/h) than in the control group (median, 9.5; IQR, 7.7–10.3 ml/kg/h) ( P  = .011). On postoperative day 1, the PaO2 /FiO2 ratio was lower in the SVV group (median, 266; IQR, 261–341) than in the control group (median, 346; IQR, 299–380) ( P  = .019). Conclusions: Use of the SVV-guided fluid management protocol did not reduce intraoperative fluid balance but increased the intraoperative fluid administration and might worsen postoperative oxygenation. Trial registration: UMIN000018111.